Alleviating Bumiputera Poverty In Sarawak: Reflections And Proposal. - Berma, Madeline; Shahadan, Faridah; Abdul Gapor, Salfarina (Universiti Sains Malaysia, 2006)
Malaysia has succeeded in reducing its overall incidence of poverty since the implementation of the New Economic Policy in 1971.